1995
DOI: 10.1007/bf01541087
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of soluble HLA class I antigens in patients with chronic hepatitis C during interferon therapy: An early predictor marker of response?

Abstract: Soluble HLA class I antigens (sHLA-I), beta 2-microglobulin (beta 2-mu) and alanine aminotransferase (ALT) serum levels have been evaluated in 16 patients affected by chronic hepatitis C treated for six months with recombinant interferon-alpha (rIFN-alpha, 3 MU three times a week). The predictor role of sHLA-I and ALT modifications with respect to the response to rIFN-alpha therapy was also evaluated. Six patients responded (group 1), five patients relapsed followed in initial responses (group 2), and five did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…In NSE-D b mice however, the NSE promoter drives the ectopic expression of the D b heavy chain in the embryonic CNS as cells differentiate into neurons. Previous studies of other tissues have found that increased MHCI expression leads to a concomitant increase in the release of sMHCI [22], [23], [24], [25]. To test whether the diffusible neuroinhibitory factor from NSE-D b thalamic tissue was soluble D b MHCI, we added a conformation-dependent anti-D b mAb to the co-cultures and observed that this rescued the ability of retinas to extend processes towards a NSE-D b thalamus (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In NSE-D b mice however, the NSE promoter drives the ectopic expression of the D b heavy chain in the embryonic CNS as cells differentiate into neurons. Previous studies of other tissues have found that increased MHCI expression leads to a concomitant increase in the release of sMHCI [22], [23], [24], [25]. To test whether the diffusible neuroinhibitory factor from NSE-D b thalamic tissue was soluble D b MHCI, we added a conformation-dependent anti-D b mAb to the co-cultures and observed that this rescued the ability of retinas to extend processes towards a NSE-D b thalamus (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Since our previous studies showed that recombinant MHCI monomers (but not heavy chain alone or β2M alone) inhibited neurite outgrowth in vitro [17], we surmised that the NSE-D b thalami were producing sMHCI which inhibited neurite outgrowth from neighboring neurons. Indeed, in other tissues, upregulated MHCI expression leads to increased release of sMHCI [22], [23], [24], [25]. However, it was also possible that the transgene in some way reduced thalamic secretion of neurotrophic factors or induced the expression of a soluble inhibitory factor(s) other than sMHCI.…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of these haplotypes, however, has yet to be elucidated (Porto et al 1998). It is interesting to note that several MHC class I and class II loci appear to contribute to SVR under interferon treatment conditions (Puppo et al 1995;Miyaguchi et al 1997;Almarri et al 1998;Kikuchi et al 1998;Sim et al 1998;Thursz et al 1999). In addition, some genes for the interferon regulatory factors, such as IRF4, located in the same chromosomal region and not very far from the HFE gene, may also contribute to this phenotype (Lebray et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports dealing with sHLA-I serum concentrations in HCV infected patients,15 16 MC was not taken into account. We observed the highest sHLA-I values in patients with type II MC.…”
Section: Discussionmentioning
confidence: 99%
“…14 High concentrations of serum HLA-class I antigens (sHLA-I) have been reported in HCV infected patients,15 16 as well as in other viral infections 1719 In HCV infection this increase could be caused by the increased endogenous production of interferons and/or other cytokines associated with viral infection, as well as by administration of interferon for therapeutic purposes 1520 and in systemic lupus erythematosus (SLE) 21.…”
mentioning
confidence: 99%